PENGARUH GAYA KEPEMIMPINAN SURYA BRATA TERHADAP KINERJA PEGAWAI DENGAN MOTIVASI KERJA YANG BERPERAN SEBAGAI MEDIASI PADA SEKRETARIAT DAERAH KABUPATEN GIANYAR - Krisna Dewi, Ni Putu; Suwandana, I Made Adi (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Ngurah Rai, 2024)
Improving employee performance is the key for organizations to achieve their vision and mission, as human resources are a vital element. The productivity of a company relies on the performance demonstrated by its employees as valuable assets that need to optimize their performance. The purpose of this study is to analyze the mediating role of work motivation in the influence of the leadership style of Surya Brata on the performance of employees in the Gianyar District Secretariat. The population in this study consisted of 104 individuals, and the sample was determined using a saturation sampling technique. The data were analyzed using the SEM-PLS technique with the assistance of SmartPLS 3 software. The results of the study indicate that the leadership style of Surya Brata has a positive and significant influence on work motivation. The leadership style of Surya Brata has a positive influence on employee performance. Work motivation has a positive and significant influence on employee performance. Work motivation is capable of mediating the influence of the leadership style of Surya Brata on the performance of employees in the Gianyar District Secretariat.